Approaches to implementing an influenza vaccine decision aid for healthcare personnel - Lam, Po-Po (University of Ottawa (Canada), 2010)
The Ottawa Influenza Decision Aid (OIDA) is a newly developed tool to assist healthcare personnel (HCP) make an informed decision regarding the seasonal influenza vaccine. The primary objective of this thesis is to determine approaches to implementing the OIDA into healthcare organizations by 1) conducting a systematic review of influenza immunization campaigns for HCP; 2) facilitating consultation meetings with healthcare organizers to collect their ideas on using the OIDA within their workplace; and 3) develop an OIDA implementation questionnaire based on the findings from the systematic review and consultation meetings. The systematic review results suggest that education-only campaigns only have a minimal impact on immunization rates. Future studies require improved reporting on the follow-up of HCP and calculation of HCP immunization rates. The consultation meetings identified ten approaches to implementing the OIDA within a healthcare setting. The OIDA Implementation Questionnaire was designed and a survey implementation approach recommended.
Keywords: Health Sciences, Epidemiology.; Health Sciences, Health Care Management.